Corporate Social Responsibility and Sustainable Development: The Review of Marketing Implicationsin NigerianTourism and Hospitality - Ariwa, Ezendu; Andrlic, Berislav; Ekwa, Hope (European Scientific Journal, ESJ, 2017)
In the past few decades tourism industry has been faced with the challenges of destination images. Much emphasis has been placed on destination positive image due to the important role it places in tourist behaviour towards choosing a destination for holiday. This study aims to investigate the perceptions of tourists about Nigeria as a leisure tourism destination. The outcome of the study shows that Nigeria has a lot of attractions that can support successful leisure tourism, but lack a strong and positive image that can act as a pull factor for its tourism demand.